Исследование нестационарного нагрева двигателя с катящимся ротором открытого исполнения - Масленников, Андрей Михайлович; Егоров, Андрей Владимирович; Дунев, Алексей Александрович; Юхимчук, Владимир Данилович (НТУ "ХПИ", 2016)
Представлена эквивалентная тепловая схема двигателя с катящимся ротором открытого исполнения для нестационарного режима работы, которая реализована в приложении Simulink Matlab. Приведены расчетные формулы для определения величин тепловых сопротивлений и теплоемкостей, входящих в состав дифференциальных уравнений, которые учитывают "пятно" контакта. Адекватность предложенной модели проверено на ДКР ВР-250/2.

Determination of the motor with a rolling rotor (MRR) heating for open type construction considering all types of power loss by using the equivalent thermal schemes (ETS) and comparing the results with experimental data. Matlab Simulink modeling of non-stationary heat mode of the MRR. In the Matlab Simulink the block diagram for the analysis of non-stationary heat motor with a rolling rotor for open type construction has been developed and implemented. The novelty of the results achieved due to considering of additional source of the heat in the contact area of rotor with stator, which should be considered while analyzing the temperature field and the thermal state as a whole. The accuracy of the equivalent thermal schemes calculation of the MRR for open type of construction allows to calculate the average values of the stator windings temperature and the stator core, as the elements with the highest value of the temperature in the motor.
Research of non-stationary heating of motor with a rolling rotor for open type of construction
Keywords: двигатель; катящийся ротор; эквивалентная тепловая схема; тепловое сопротивление; теплоемкость; уравнения дифференциальные; "пятно" контакта